Gli enti locali e le limitazioni del diritto alla libertà religiosa: il divieto di indossare il velo integrale (Stato, Chiese e pluralismo confessionale, 2016)
SOMMARIO: 1. Introduzione: il velo nello Stato multiculturale - 2. La “prima ondata” di ordinanze anti-velo e la sentenza n. 3076 del 2008 del Consiglio di Stato - 3. I casi di compressione legittima del diritto alla libertà religiosa individuati dalla sentenza n. 3076 del 2008 - 4. La “seconda ondata” di ordinanze anti-velo e la proposta di modifica della legge n. 152 del 1975 – 5. La “terza ondata” di provvedimenti anti-velo in seguito agli attentati di Parigi del novembre 2015 - 6. Conclusioni: quale margine per un divieto di indossare il velo integrale nell’ordinamento italiano? Local government bodies and the compression of freedom of religion: the ban on the face veil.ABSTRACT: During the last decade several Italian local government bodies (and especially Municipalities) attempted to introduce a general ban on the so called “face veil” (niqab or burqa) through secondary law, in the absence of a national comprehensive policy on the matter. The aforementioned attempts were, without fail, found illegal by the Council of State and the Constitutional Court. Nonetheless, following the rekindling of the anti-Islamic sentiment in Europe in the aftermath of the 2015 terrorist attacks in Paris, we are currently witnessing a “new wave” of local regulation trying to impose a ban on the face veil, based on the claim that, in order to answer the exacerbation of the so called “clash of cultures”, a different balancing of the fundamental rights involved is needed. The author challenges the legality of the new local bans, as well as the compatibility of a general ban on the face veil with the Italian constitutional system.